Declining population of giant clams (Cardiidae: Tridacninae) in Palawan, Philippines (Ocean and Coastal Research, 2024)
For more than two decades, the Philippine government has protected the giant clams (Bivalvia: Cardiidae:Tridacninae) from exploitation and trade. However, there still is lack of information on the impact of these protectivemeasures in conserving the species richness and density, especially in Palawan, the country’s last strongholdof these reef-associated bivalves. Hence, to assess the species richness and density of giant clams in Palawan,we conducted 57 photo-transect surveys in six sites covering 12,325 m2. Out of these transect, 15 measured 5× 25 m and the rest measured 5 × 50 m. For historical trends in the population of giant clams in Palawan, weused six published papers obtained from online platforms, 13 reports, and five undergraduate theses archivedin local libraries. Information derived from recent field surveys indicated high variations in species richness (2 to5 species) and densities (0.1 to > 3.6 ind.100 m-2). Historical data starting from 1984, including recent fieldwork,indicated very low densities and a declining trend. The current status suggests that giant clam populations’viability and the reefs’ health are threatened. Effective mechanisms are needed to safeguard and enhance theremaining giant clam populations.